DETERMINATION OF HEAVY METALS AND TOTAL PETROLEUM HYDROCARBONS IN SOIL SAMPLES AND PLANT LEAVES AROUND OIL REFINERIES LOCATED ON ERBIL-GWER ROAD - Hama Kareem, Karwan K.; Abdulla , Siraj S. (Science Journal of University of Zakho, 2023)
Several refinery complexes exist in the Kurdistan Region of Iraq that produce various kinds of petroleum products. During the refining process, different types of gases, metals, hydrocarbons, and liquids are discharged into the environment. This study aimed to determine the concentration of eight heavy metals in soil and plant leaves collected around the refineries along Erbil-Gwer Road on two occasions throughout the study period. Additionally, we aimed to evaluate the levels of Total Petroleum Hydrocarbons (TPH) in the soil samples from the area. The results of the analysis revealed significant differences (P Cr> Zn> Ni> Cu> Pb> As> Cd in successive forms. Regarding the plant leaves, significant differences (P
Keywords: Oil Refineries; Heavy metal; TPH; Soil; Plant leaves; XRF